"I Just Felt Like I Was in a Cage": Examining the Accounts of Returned Missing Adults With Mental Health Issues. (January 2017) - Holmes, Lucy
"It's not waiting to be found, not missing, not lost or anything like that—just not wanting to be found for a while" [Formerly missing woman]. When an adult goes missing, there is often an underlying reason; save for a small number of misunderstandings, missing incidents tend to be indicative of difficulties in the missing person's life. Mental health is inextricably linked with missing; as many as 80% of missing people are thought to have a mental health issue (Holmes, 2014b). Using data collected by the Economic and Social Research Council-funded Geographies of Missing People project, this article explores this link, through secondary analysis of interviews with returned missing adults and with police officers, to shine a light on the key themes that emerged. Furthermore, the article argues that the response to returning missing adults in the United Kingdom is inadequate, meaning that potentially vulnerable adults are left without the assessment and support they need to maintain their mental well-being and to prevent future missing incidents. This article contributes to existing knowledge about the links between mental health and missing and makes a number of suggestions for improvements in cross-sector policy and practice.